Proceedings of the 1998 IEEE International Conference on Acoustics, Speech and Signal Processing, ICASSP '98 (Cat. No.98CH36181
DOI: 10.1109/icassp.1998.681659
|View full text |Cite
|
Sign up to set email alerts
|

Generalized forward/backward subaperture smoothing techniques for sample starved STAP

Abstract: A major issue in space-time adaptive processing (STALP) for airborne moving target indicator (MTI) radar is the so-called sample support problem. Often, the available sample support for estimating the interference covariance matrix leads to severe rank deficiency, thereby precluding STAP beamforming based on the direct sample matrix inversion (SMI) method. The intrinsic mterference subspace removal (ISR) technique, which is a computationally useful form of diagonally loaded SIMI method, can handle this case, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…where f 1 (z; M 1 , H 1,1 |α) is the conditional pdf of z given α. Taking the negative logarithm, problem (27) is equivalent to…”
Section: B Nljs and Coherent Interferers Joint Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…where f 1 (z; M 1 , H 1,1 |α) is the conditional pdf of z given α. Taking the negative logarithm, problem (27) is equivalent to…”
Section: B Nljs and Coherent Interferers Joint Attackmentioning
confidence: 99%
“…As an illustration of this fact, consider those decision rules devised assuming that the ICM is centrohermitian. These algorithms allow us to reduce the number of training samples required for the ICM estimation [16]- [23], [27], [28] by almost a half while maintaining a satisfactory detection performance. Further examples are provided in [24], [25], where it is shown that the spectral symmetry of the clutter can be used for instance to obtain gains of about 3 dB (in SINR, namely Signal-to-Interference plus Noise Ratio), for a Probability of Detection P d = 0.9 and Probability of False Alarm P f a = 10 −4 , in comparison to conventional detectors.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that the persymmetric structure is not limited to linear arrays but it can be found in different geometries such as standard rectangular arrays, uniform cylindrical arrays (with an even number of elements), and some standard exagonal arrays [16]. Several approaches, relying on the persymmetry, have been developed to achieve improved detection performances in training-limited scenarios; just to give some examples, see [17]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…Joint spatial-temporal processing addresses this issue [18] and many algorithms for space-time adaptive processing (STAP) have been developed [11]. Of particular interest are algorithms requiring minimal data for the estimation of covariance matrices needed for STAP [12,16].…”
Section: Introductionmentioning
confidence: 99%